Effect of Operant Conditioning in an Athetoid for Improving Dexterity - Hosakote, Vidya (Journal of All India Institute of Speech and Hearing)
Operant conditioning procedures have been applied to improve verbal ex- pression of non-verbal children, aphasics, (Kerr, et al 1965, Dembros 1966), elective mutism cases, stutterers and schizophrenics to improve work skills (Girerdean and Spradlin, 1964, Bensberg, 1965, etc.)